Reconnection and Revitalisation: from Warwick Junction to the Waterfront (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2018)
Durban is a cogent city in its planning. However, it has a colonial history which is expressed in its urban quality. The city is also a modern city defined by segregation of functions. The post-apartheid period resulted in the change in socio-economic dynamics of the city which raises many challenges while it affords various opportunities for development and enhancement through architectural and urban design intervention. The project developed during the workshop held at Durban University of Technology, prior to the UIA 2014 conference focused on the development of design concepts for responsive urban revitalisation.